Crash Analysis of the Frontal Structure of a Car Using Explicit Dynamics (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Crash analysis is the primary test conducted to determine crashworthiness and eliminate safety concerns in avehicle. The improvements in roadways and implementation of new design technologies in automobiles, has shifted atremendous focus on vehicle safety in recent years. Deaths due to road accidents over the years have increased, primarily dueto the inability of a car to withstand load and impact forces during collision. Multiple tests to assign passenger cars with aGlobal New Car Assessment Program rating (NCAP) have been conducted and the result is still inconsequential. This studypresents a comparative outlook for a more structurally suitable material. Materials were selected based on previous researchconducted. Three different velocities of 40 km/hr, 80 km/hr, 120 km/hr were considered and a simulation to calculate TotalDeformation, Equivalent Plastic Strain and Equivalent Stress (Von Mises) was carried out using Explicit Dynamics inANSYS. Values calculated at these velocities are presented in a tabular form and graphs were made. Inference was drawnand a suggestion for a better material is made.